Measuring laziness through self-regulation using heart rate variability (HRV) biofeedback - Wan Rusyaini, Wan Mohd (2015)
Laziness becomes a common behavior among students in the learning processes and cognitive performance. This behavior appears within a person because of the failure in self-regulation and he/she normally experiences lack of achievement goal orientationsin studies. As a result, lazy students have low enthusiasm in their way of thinking, tendency, habits and behavior. Thus, this study measuredlaziness through self-regulation by using heart rate variability (HRV) biofeedback technique. The objectives of this research are to design and test the biofeedback script as a measurement of their self-regulation’s ability and to compare the HRV coherence score between low and good academic performances.Samplesconsisted of 20 students at the age of sixteen with different background of academic performances. They are assigned as the clinical experimental group (n=20)usingemWave® PC Stress ReliefSystemsoftwaredeveloped by Quantum Intech, Inc. The samples received one session of clinical experiment consists of four protocolsHRV biofeedback training within the duration of 12-20 minutes each. They were stimulated using the self-regulation script in the baseline, pre-recorded zikr, self-zikrand self-talk protocols. The self-regulation script was used to test their self-control to maintain the targeted goal of 100% LF (low frequency) coherence score. They were being taught on the method to achieve the targeted goal by implementing the diaphragmatic breathing technique and reciting the zikr of Lailahailallah. By using the Mann-Whitney t-test, One-Way ANOVA and Tukey’s HSD Post Hoc test it was shown that the low academic performances have higher VLF (very low frequency) coherence score compared to the good academic performances. The higher scores in the VLF coherence score indicated that the low academic failed to apply the method of increasing the LF score. Thus, it showed that they failed to self-regulate themselves and were lazy to achieve the targeted goal. Meanwhile,the good academic performance could be categorized as the self-regulated when they successfully achieved the targeted goal in all protocols. They demonstrated persistence during the clinical experimental sessions. Through self-regulation,in terms of effort and persistence towards targeted goal, the levels of laziness were being investigated among different groups of academic performances.Results from the Mann-Whitney t-test showedthat there was a significant difference in VLF Self-Zikr (p=0.05) where the mean value of low academic performance was higher compared to the good academic performance. The t-testrevealed that the low academic performance failed to achieve the targeted goal which explained their low level of self-regulation. The LF activity was higher for the good academic performance in the biofeedback training using diaphragmatic breathing technique, zikr and self-regulation script. As a summary, low academic performances group demonstrated higher level of laziness compared tothe good academic performances. Their performance and effort enhancement in the clinical experimental explained the levels of self-regulation which described their laziness.